Evaluasi Sistem Informasi Permohonan Elektronik Menggunakan Metode Pieces - Destinaya, Irtiyah Daniyah; Wulandari, Siska; Irawan, Debi; Gunawan, Syam; Iqbal, Muhammad (Institut Informatika Dan Bisnis Darmajaya, 2025)
Advances in digitization within government institutions have encouraged the development of more efficient and transparent electronic services. This study aims to evaluate the Electronic Application Information System (SIMPEL) of the Constitutional Court of the Republic of Indonesia using the PIECES framework. This study involved 112 respondents, consisting of Applicants/Community (53.6%), Civil Servants (20.5%), Advocates/Legal Representatives (17%), and other user categories (8.9%). The method used was quantitative descriptive with data collection through online surveys and statistical analysis using SPSS version 26.0. The results showed that the Economy dimension received the highest score of 4.26, while the Control dimension received the lowest score of 3.75, indicating the need to improve system security. In practical terms, these findings confirm the need to strengthen two-factor authentication (2FA), tighten access control, and optimize file validation to minimize the risk of data leaks and unauthorized access. This research contributes to the development of digital public services that are more secure, efficient, and user-oriented, as well as enriching the evaluation of e-government systems in Indonesia.